How Learning from Trauma Benefits the Obstetric Population? Damage Control Surgery - Dandan Shi; María Fernanda Escobar Vidarte; Daniela Nasner; Albaro José Nieto-Calvache; María Paula Echavarría; Javier Andrés Carvajal (Maternal-Fetal Medicine)
Abstract. The recent implementation of trauma-validated damage control strategies in severe postpartum hemorrhage proves the importance of interdisciplinary management in the obstetric patient. Massive hemorrhage control techniques and damage control surgery are clear examples of how learning from trauma can benefit the obstetric population. Currently, most obstetric programs do not include training in this type of interventions. Nevertheless, it has been shown that these interventions are useful in the management of severe postpartum hemorrhage. The aim of this article is to introduce the application of damage control surgery principles in the management of massive obstetric hemorrhage. We propose to include appropriate training and the implementation of damage control surgery in obstetric management protocols. The prompt application of damage control principles can be considered in patients with persistent hemodynamic instability despite control of the source of bleeding.